The Discovery of Chicken Foxp3 Demands Redefinition of Avian Regulatory T Cells - Burkhardt, Nina B; Elleder, Daniel; Schusser, Benjamin; Krchlíková, Veronika; Göbel, Thomas W; Härtle, Sonja; Kaspers, Bernd (Journal of immunology (Baltimore, Md., 2022)
Since the publication of the first chicken genome sequence, we have encountered genes playing key roles in mammalian immunology, but being seemingly absent in birds. One of those was, until recently, Foxp3, the master transcription factor of regulatory T cells in mammals. Therefore, avian regulatory T cell research is still poorly standardized. In this study we identify a chicken ortholog of Foxp3 We prove sequence homology with known mammalian and sauropsid sequences, but also reveal differences in major domains. Expression profiling shows an association of Foxp3 and CD25 expression levels in CD4+CD25+ peripheral T cells and identifies a CD4-CD25+Foxp3high subset of thymic lymphocytes that likely represents yet undescribed avian regulatory T precursor cells. We conclude that Foxp3 is existent in chickens and that it shares certain functional characteristics with its mammalian ortholog. Nevertheless, pathways for regulatory T cell development and Foxp3 function are likely to differ between mammals and birds. The identification and characterization of chicken Foxp3 will help to define avian regulatory T cells and to analyze their functional properties and thereby advance the field of avian immunology.
Keywords: Sequence Homology; Sequence Analysis, DNA; sekvence aminokyselin; Gene Expression Profiling; Cell Differentiation; Sequence Alignment; forkhead transkripční faktory; regulační T-lymfocyty; receptor interleukinu-2 - alfa-podjednotka; kur domácí; Genome; T-Lymphocytes, Regulatory; Base Sequence; sekvence nukleotidů; aktivace lymfocytů; Chickens; Forkhead Transcription Factors; zvířata; Lymphocyte Activation; Amino Acid Sequence; genom; sekvenční analýza DNA; Interleukin-2 Receptor alpha Subunit; stanovení celkové genové exprese; sekvenční homologie; buněčná diferenciace; sekvenční seřazení; Animals